2022
DOI: 10.3390/ijerph19094958
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Dissolved Organic Matter Characteristics Released from Sediment According to Precipitation in the Namhan River with Weirs: A Laboratory Experiment

Abstract: In this study, changes in the properties of dissolved organic matter (DOM) released from sediments into water layers were investigated. To analyze the spatial and temporal variation in dissolved organic carbon (DOC), sediment and bottom water samples were collected upstream of the Gangcheon, Yeoju, and Ipo weirs of the Namhan River during the rainy and non-rainy seasons. The initial DOC was correlated with precipitation (R2 = 0.295, p = 0.034) and residence time (R2 = 0.275, p = 0.040). The change in the botto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…The specific UV absorbance at 254 nm (SUVA 254 ) was defined as the UV absorbance coefficient (m −1 ) at 254 nm divided by the DOC concentration (mg/L) [23]. Oh and Choi [24] found that SUVA 254 was high when high-molecular-weight natural organic matter flowed into rivers through rainfall and runoff. The spectral slopes for the wavelength intervals of 275-295 nm (S 275-295 ) and 350-400 nm (S 350-400 ) were obtained using linear regression of the natural log-transformed absorption spectra [25].…”
Section: Uv-visible Absorption Spectroscopymentioning
confidence: 99%
“…The specific UV absorbance at 254 nm (SUVA 254 ) was defined as the UV absorbance coefficient (m −1 ) at 254 nm divided by the DOC concentration (mg/L) [23]. Oh and Choi [24] found that SUVA 254 was high when high-molecular-weight natural organic matter flowed into rivers through rainfall and runoff. The spectral slopes for the wavelength intervals of 275-295 nm (S 275-295 ) and 350-400 nm (S 350-400 ) were obtained using linear regression of the natural log-transformed absorption spectra [25].…”
Section: Uv-visible Absorption Spectroscopymentioning
confidence: 99%
“…The speci c UV absorbance at 254 nm (SUVA 254 ) was de ned as the UV absorbance coe cient (m − 1 ) at 254 nm divided by the DOC concentration (mg/L) (Weishaar et al, 2003). Oh and Choi (2022) found that SUVA 254 was high when high-molecular-weight natural organic matter owed into rivers through rainfall and runoff. The spectral slopes for the wavelength intervals of 275-295 nm (S 275 − 295 ) and 350-400 nm (S 350 − 400 ) were obtained using linear regression of the natural log-transformed absorption spectra (Helms et al, 2008).…”
Section: Uv-visible Absorption Spectroscopymentioning
confidence: 99%